Pengembangan e-Modul Berbasis Discovery Learning Dengan Bantuan Flip PDF Corporate Edition pada Materi Ikatan Kimia - Clarisa Yesilia Br Simanjuntak; Jamalum Purba (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2024)
The aim of this research is to determine the feasibility of a discovery learning-based e-module on chemical bonding material developed in accordance with the requirements of the BSNP criteria and students' responses to the discovery learning-based e-module on chemical bonding material developed. The research method used is Research & Development (R&D) with a 4D model consisting of define, design, develop and disseminate stages. However, this research was limited to the development stage. The instruments used are validation sheets and student response questionnaires. The results of the research show that the e-module based on discovery learning on chemical bonding material that was developed meets the very valid criteria with a percentage of content suitability aspects of 94.45%, presentation suitability of 96.67%, language suitability of 94.82%, and graphic suitability of 86.19%, while response students amounted to 91.52%. From the results of this research, it can be concluded that the e-module based on discovery learning on chemical bonding material that has been developed has very good quality and can be used to support learning.